Glaucoma management in Sweden – results from a nationwide survey - Lindén, Christina (Blackwell Publishing Ltd, 2013)
PURPOSE: To report the results from a nationwide survey on glaucoma management in Sweden, performed as a part of an Open Angle Glaucoma project conducted by the Swedish Council on Health Technology Assessment 2004–2008. METHODS: In 2005, a survey was distributed to all providers of glaucoma care in Sweden: public eye departments, public outpatient departments and private practices. The questionnaire included questions on number of examined patients, types of examinations during one defined week, internal organization and access to diagnostic equipment. The questionnaire was endorsed by the Swedish Ophthalmological Society. Reminders were sent out to nonresponders. RESULTS: Response rate was high; 97% (33/34) of eye departments, 85% (39/46) of outpatient departments and 55% (69/125) of private practices. Out of 29 282 visits in ophthalmic care during the study week, 7737 (26%) were related to glaucoma. Diagnostic equipment was generally available; all public eye facilities and 92% of private practices had at least one computerized perimeter, while equipment for fundus photography/imaging was available at 100% of eye departments, 82% of outpatient departments and 62% of private practices. The number of visual field tests and fundus images was rather low. Survey results indicate that patients on the average underwent bilateral field testing every 2nd year and fundus imaging every 8th year. CONCLUSION: Glaucoma care generated about a quarter of all patient visits in Swedish ophthalmic care. Access to diagnostic facilities was good. To meet modern standards of glaucoma care, glaucoma damage must be measured and followed more closely than at the time of the survey.